"Mister, you're writing in Spanglish": Fostering spaces for meaning making and metalinguistic connections through teacher translanguaging shifts in the bilingual classroom. Issue 3 (3rd July 2018) - Henderson, Kathryn I.; Ingram, Mitch
ABSTRACT: We examine how a third-grade bilingual teacher engaged in translanguaging shifts —the moment-to-moment changes in language practices—during instruction in response to students' language performances. We demonstrate how a teacher's high level of multilingual awareness connected to fostering classroom spaces with linguistic flexibility that leveraged translanguaging practices as a resource. We present pedagogical practices of teacher translanguaging used intentionally for access to academic content, the cultivation of classroom community, and development of student metalinguistic awareness. This case study adds information about translanguaging in a bilingual classroom with implications for the role of teacher critical multilingual awareness within a translanguaging pedagogical framework.